1968
DOI: 10.1159/000458241
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Small Intestine in the Disposal of Enzymes from Blood

Abstract: Summary. The transfer of intravenously injected enzymes from blood to Thiry- Vella fistulas of the small intestine was studied in dogs. The enzymes used were highly purified preparations of glutamic-pyruvic transaminase and two glutamicoxalacetic transaminases. The rate of transfer varied greatly, depending on whether isotonic or hypertonic solutions were placed inside the loop. On the other hand, there was relatively little difference in the transfer of the three enzymes, although their plasma-disappearance h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

1968
1968
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…Rotenone-insensitive NADH cytochrome c reductase activity was determined by the method of Dallner et al [26]. UDP-galactose: N-acetylglucosamine galactosyltransferase activity was determined by the method of Fleisher [27]. Glucose transport Glucose transport was assayed by measuring initial rates of 3-O-methylglucose influx.…”
Section: Fractionation Of Adipocytesmentioning
confidence: 99%
“…Rotenone-insensitive NADH cytochrome c reductase activity was determined by the method of Dallner et al [26]. UDP-galactose: N-acetylglucosamine galactosyltransferase activity was determined by the method of Fleisher [27]. Glucose transport Glucose transport was assayed by measuring initial rates of 3-O-methylglucose influx.…”
Section: Fractionation Of Adipocytesmentioning
confidence: 99%
“…Os indicadores bioquímicos CK e AST utilizados no presente estudo constituem marcadores de lesão muscular, dado o facto de serem proteínas que, quando libertadas para o espaço extracelular, em resposta ao exercício físico, permitem determinar, ainda que de forma indirecta, a existência de lesões [3,5]. As enzimas ALT e GGT encontram-se em maior concentração no fígado e epitélios dos ductos biliares e renais, respectivamente [18], o que pode sugerir a possibilidade de lesão hepática, quando observado um aumento significativo dos níveis séricos destas enzimas em resposta ao exercício físico [19].…”
Section: Discussionunclassified
“…This is indicated by the concentrations of radioactivity in the spleen and liver, comparable at 2 h and 8 h with that of the plasma, and the appreciable amounts in the tissue and lumen of the small intestine. Fleisher & Wakim (1968) demonstrated that the small intestine contributes to the clearance of injected alanine transaminase in the dog, and it is well established that the gastrointestinal tract plays a part in the elimination of plasma albumin (Armstrong, Margen & Tarver, 1960;Wetterfors, Gullberg, Liljedahl, Plantin, Birke & Olhagen, 1960;Ullberg, Birke, Ewaldsson, Hansson, Liljedahl, Plantin & Wetterfors, 1960;Glenert, Jamum & Riemer, 1962;Jeejeebhoy, Jarnum, Singh, Nadkarni & Westergaard, 1968;Skala, Vesely & Petrus, 1972).…”
Section: Discussionmentioning
confidence: 99%